Influence of acute dietary nitrate supplementation on 50 mile time trial performance in well-trained cyclists - Wilkerson, D. P.; Hayward, G. M.; Bailey, S. J.; Vanhatalo, A.; Blackwell, J. R.; Jones, A. M. (European Journal of Applied Physiology, 2012)
Dietary nitrate supplementation has been reported to improve short distance time trial (TT) performance by 1-3 % in club-level cyclists. It is not known if these ergogenic effects persist in longer endurance events or if dietary nitrate supplementation can enhance performance to the same extent in better trained individuals. Eight well-trained male cyclists performed two laboratory-based 50 mile TTs: (1) 2.5 h after consuming 0.5 L of nitrate-rich beetroot juice (BR) and (2) 2.5 h after consuming 0.5 L of nitrate-depleted BR as a placebo (PL). BR significantly elevated plasma [NO2 -] (BR: 472 ± 96 vs. PL: 379 ± 94 nM; P < 0.05) and reduced completion time for the 50 mile TT by 0.8 % (BR: 136.7 ± 5.6 vs. PL: 137.9 ± 6.4 min), which was not statistically significant (P > 0.05). There was a significant correlation between the increased post-beverage plasma [NO2 -] with BR and the reduction in TT completion time (r = -0.83, P = 0.01). Power output (PO) was not different between the conditions at any point (P > 0.05) but oxygen uptake ( VO2) tended to be lower in BR (P = 0.06), resulting in a significantly greater PO/ VO2 ratio (BR: 67.4 ± 5.5 vs. PL: 65.3 ± 4.8 W L/min; P < 0.05). In conclusion, acute dietary supplementation with beetroot juice did not significantly improve 50 mile TT performance in well-trained cyclists. It is possible that the better training status of the cyclists in this study might reduce the physiological and performance response to NO3 - supplementation compared with the moderately trained cyclists tested in earlier studies.